Forestry in Soil Conservation - Sen, N N (Journal of Soil and Water Conservation, 2022)
Although it may be a matter of contro- versy whether grassland is more helpful as protective soil cover than the tree growth, all of you will probably agree that forests in sloping lands play a very great part in the conservation of soil and water. Destruction of soil cover in sloping land, particularly when the gradient is steep, has caused im- measurable miseries to the people inhabiting the valleys. The devastation that is caused every year by the floods of the Kosi and the Gandak over vast areas of Bihar, U.P. and Nepal is the direct result of the destruction of the forest cover in the catchment areas of these great rivers. The destruction of Siwalik forests in Hoshiarpur district had caused great havoc in the valley lands. The areas covered by the chos in 1852 was 75 sq. miles, which extended to more than 700 sq. miles by 1939 and, therefore, Government had to take recourse to cho reclamation mea- sures on an extensive scale to protect what- ever was left of the devastation. Year after year devastating floods were being caused by the Damodar and its tributaries in West Bengal bringing miseries to millions in its wake. This has given rise to the Damodar Valley Corporation.